Analisis Pembelajaran dengan Pendekatan TARL pada Hasil Belajar Matematika Peserta Didik Kelas X MPLB 2 di SMK N 2 Semarang - Rona Indah Melati Sukma; Heni Purwati; Amanati Rochmah; Muhtarom Muhtarom (Departement of Mathematics Education, 2024)
This research aims to evaluate the effectiveness of implementing the Teaching at the Right Level (TaRL) approach in improving mathematics learning outcomes in class X MPLB 1 SMK N 2 Semarang. The TaRL approach places students in groups based on their ability level, not based on grade level or age, to ensure each student receives learning appropriate to their abilities. This research uses a descriptive-qualitative approach with a retrospective case study method. Data collection was carried out through observation, closed interviews using Google Forms, and documentation. Learning activities were carried out over two meetings in October 2024. At the first meeting, students were introduced to the TaRL approach and carried out a pre-test to measure their initial abilities. The pre-test results show that the majority of students still get scores below the Minimum Completeness Criteria (KKM). During the learning process, students are divided into groups based on their ability level to improve learning through discussion and collaboration. At the second meeting, students showed increased activity and higher enthusiasm for learning. At the end of the lesson, a post-test is carried out to measure the increase in student learning outcomes. The post-test results showed a significant increase in understanding of the material compared to the pre-test results. In addition, closed interviews show that students feel comfortable and happy with the TaRL method, which makes learning more interesting and easy to understand. The results of this research indicate that the TaRL approach is effective in improving students' mathematics learning outcomes, engagement, and learning motivation. The TaRL approach can be considered an effective and innovative model to be applied in other classes to achieve optimal learning outcomes.